Governance and the economy in Asia and the United States: institutions, instruments and reform. Issue 1 (2nd January 2016) - Knott, Jack H.
Abstract : Effective governance involving the use of various institutions and instruments is very important for economic development. While many states fail to achieve even the minimal features of effective governance, state capitalism has proven to be a successful model economically. The problem is that state capitalism is frequently associated with authoritarian and corrupt regimes. Over time, such regimes limit economic efficiency, ignore the environment, and under-invest in social and health services. In the West and some Asian countries, these conditions have led to substantial reform in democratic governance. Singapore and possibly the People's Republic of China offer alternative models of reform, reducing corruption and somewhat liberalising their economies in the absence of well-developed democratic governance.